Exploring Jesus' Teaching Methods: Effective Strategies for 21st-Century Education - Liud, Yahya Herman; Atang, Johan; Nendissa, Julio Eleazer (Jurnal Didaskalia, 2024)
21st-century education is a process of enhancing both the quantity and quality of overall talent or potential, empowering individuals to develop better personal character so that the knowledge gained can be applied in their lives. This paper aims to explore how Jesus' teaching methods can be applied as an effective strategy for 21st-century education. 21st-century education encourages educators to utilize technology as a medium for learning, where the learning process and outcomes focus not only on the results achieved but also on the classroom learning process. This study employs a qualitative research method based on a literature review to analyze the issues the author wishes to investigate. The findings of the research indicate that educators should emulate and adopt Jesus' teaching methods by utilizing technology as a means of delivering education to students, particularly in the field of Christian religious education. This approach can effectively transfer knowledge about Christian teachings, thereby enhancing students' faith and spirituality to meet the challenges of the 21st century. Therefore, educators must strive to educate students to keep up with the developments of the 21st century, fostering critical thinking, creativity, communication skills, all based on the Word of God and the fear of God.